217k views
5 votes
40+[3{18÷(9-3)-11-9}+4]​

User Divyu
by
5.5k points

2 Answers

3 votes

Answer:


\sf \large \: - 7

Explanation:

40+3(18/9−3−11−9)+4

=40+3(18/6−11−9)+4

=40+3(3−11−9)+4

=40+3(−8−9)+4

=40+(3)(−17)+4

=40+−51+4

=40+−47

=−7

3 votes

Explanation:

= 40 + [ 3 { 18 ÷ ( 9 - 3 ) - 11 - 9 } + 4 ]

= 40 + [ 3 { 18 ÷ 6 - 11 - 9 } + 4

= 40 + [ 3 { 3 - 20 } + 4

= 40 + [ 3 {- 17 } + 4

= 40 + ( - 51 ) + 4

= 40 + 4 - 51

= 44 - 51

= - 7


...

☘☘☘....

User Paul Evans
by
4.4k points